2009
DOI: 10.1021/nl9017594
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystalline Mesoporous Silicon Nanowires

Abstract: Porous semiconductors have garnered significant attention for their novel chemistry and potential applications as high surface area and optically active substrates [ 1-5 ]. Porous silicon in particular has long been studied for its potential applications in optoelectronics and sensing as a result of its light-emitting properties [ 6-10 ]. In addition, they can also serve as drug or gene delivery matrix because of their good biocompatibility [11][12] . Porous silicon is typically synthesized by applying a volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
318
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(352 citation statements)
references
References 26 publications
24
318
1
Order By: Relevance
“…Facile methods such as electroless etching [30][31][32][33][34][35][36][37][38][39][40][41] and electrochemical etching [42][43][44][45][46][47][48] are able to convert bulk silicon wafer into a porous structure with tunable pore size and porosity, which is called 'integral' porosity. For example, with an appropriately doped Si wafer, porous Si and Si nanowires can be synthesized in the presence of silver nitrate (AgNO3) in hydrofluoric acid (HF) etchant solution.…”
Section: Silicon Wafermentioning
confidence: 99%
“…Facile methods such as electroless etching [30][31][32][33][34][35][36][37][38][39][40][41] and electrochemical etching [42][43][44][45][46][47][48] are able to convert bulk silicon wafer into a porous structure with tunable pore size and porosity, which is called 'integral' porosity. For example, with an appropriately doped Si wafer, porous Si and Si nanowires can be synthesized in the presence of silver nitrate (AgNO3) in hydrofluoric acid (HF) etchant solution.…”
Section: Silicon Wafermentioning
confidence: 99%
“…This method has been widely studied for the synthesis of silicon nanowires starting from various types of silicon wafers with different doping levels and orientations, including lightly and highly doped p-type Si(100) and Si(111) wafers, lightly doped n-type Si(100) and Si(111) wafers and Si(110) and Si(113) wafers. [41][42][43][44][45][46][47][48][49][50][51][53][54][55][56][57][58] The metal-assisted chemical etching reactions can be classified into two types: one-step reaction and two-step reaction. Recent reports show that single crystalline porous silcion nanowires have been synthesized through both one-step and two-step reactions by adjusting the reaction conditions.…”
Section: Synthesis Of Porous Silicon Nanowires and The Mechanismmentioning
confidence: 99%
“…Recent reports show that single crystalline porous silcion nanowires have been synthesized through both one-step and two-step reactions by adjusting the reaction conditions. [41][42][43][44][45][46][47][48][49][50][51] Highly Doped p-type Si (100) Wafer 43 One-step chemical etching involves the immersion of clean p-type silicon substrates in an etchant solution containing 0.01-0.04 M AgNO 3 and 5 M HF. It was found that the surface morphology of the as-synthesized silicon nanowires was highly dependent on the resistivity of the original silicon wafers.…”
Section: Synthesis Of Porous Silicon Nanowires and The Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the preparation methods for such nanostructures [11,12], metalassisted chemical etching is well-received as one of the viable technique to produce highly ordered Si nanostructure arrays, as this simple technique is effective and cost effective. Porous silicon nanowires (PSiNWs) prepared by metal-electroless etching technique (13,14) have been widely explored as an alternative top-down route for the fabrication of nanostructures that give visible light emission and good electronic transport properties [15,16]. In this paper, we study the morphology of PSiNWs and the optical properties of this nanostructures.…”
Section: Introductionmentioning
confidence: 99%